Molecular insights into human phosphatidylserine synthase 2 and its regulation of SREBP pathways - Dongyu Li; Hongwen Chen; Goncalo Vale; Nadia Elghobashi-Meinhardt; Alexandra Hatton; Shunxing Rong; Jeffrey G. McDonald; Xiaochun Li (Proceedings of the National Academy of Sciences, 2025)
Homologous proteins share similar sequences, enabling them to work together in cells to support normal physiological functions. Phosphatidylserine synthases 1 and 2 (PSS1 and PSS2) are homologous enzymes that catalyze the synthesis of phosphatidylserine (PS) from different substrates. PSS2 shows a preference for phosphatidylethanolamine (PE) as its substrate, whereas PSS1 can utilize either PE or phosphatidylcholine. Previous studies showed that inhibiting PSS1 promotes SREBP-2 cleavage. Interestingly, despite their homology, our findings reveal that PSS2 exerts an opposing effect on the cleavage of both SREBP-1 and SREBP-2. We resolved the cryo-electron microscopy (cryo-EM) structure of human PSS2 at 3.3 Å resolution. Structural comparison of the catalytic cavities between PSS1 and PSS2 along with molecular dynamics simulations uncovers the molecular details behind the substrate preference of PSS2 for PE. The lipidomic analysis showed that PSS2 deficiency leads to PE accumulation in the endoplasmic reticulum, which has been shown to inhibit the cleavage of sterol regulatory element-binding proteins (SREBPs) in mice. Thus, our findings reveal the intricate network of intracellular phospholipid metabolism and underscore the distinct regulatory roles of homologous proteins in cellular activities.